The effect of peri-intraventricular hemorrhage on the auditory pathway of infants - da Silva, Leticia Saia [UNESP]; Ribeiro, Georgea Espindola [UNESP]; Montovani, Jair Cortez [UNESP]; Silva, Daniela Polo Camargo da [UNESP] (Elsevier, 2018)
Objective: To verify the effect of peri-intraventricular hemorrhage on the auditory pathway of preterm infants. Method: It is a non-concurrent cohort study. This study was conducted in a tertiary public. Preterm infants with peri-intraventricular hemorrhage comprised the study group, and preterm infants without peri-intraventricular hemorrhage were included as a comparison group, both were similar in relation to gestational age and risk indicators for hearing loss. Participants had to meet the following inclusion criteria: have been born at the study site, presence of otoacoustic emissions by transient stimulus in both ears and brainstem auditory evoked potentials with all components bilaterally identified. Results: 44 infants with an average age of 3 months with peri-intraventricular hemorrhage and 2,6 months without peri-intraventricular hemorrhage met the inclusion criteria. Regarding the brainstem auditory evoked potentials results, a significant increase was observed in absolute latency values of waves I, III and V, as well as in the interpeak intervals I-III and I-V, bilaterally, in infants with peri-intraventricular hemorrhage. Conclusion: This study concluded that infants with peri-intraventricular hemorrhage presented a delay in the neural conduction of sound, which justifies the monitoring of the auditory function in these infants during the period of language development.
Keywords: Electrophysiology; Hearing loss; Neonatal screening; Newborn